Development and stability of an anti-aging gel with hydroalcoholic extract from Salvia SP - Favero, Yonah (2021)
Introduction: The incessant search for products from nature to apply in the search for treatment, cure or even the well-being associated with the aesthetics itself, has strongly collaborated to deepen the area of study and knowledge, so as to meet the demands of the world population. Objectives: This work aimed at the development and evaluation of the stability of two gels formulations (carbopol and methylcellulose) from the incorporation of the essential oils of the species S. officinalis and S. elegans and their hydroalcoholic extract. Methods: Physicochemical stability, organoleptic gel tests, eye irritability test (HET-CAM test) and Clevenger hydrodistillation were performed to determine the oil yield and to use them as a natural preservative in the gels. Results: As significant results we have: In light cycle tests there was only a color change after 15 days. In freeze / thaw tests there was a change in carbopol gel for S. officinalis in appearance and for S. elegans in pH and appearance, whereas in methylcellulose gel in S. elegans there was only change in pH. The accelerated stability test showed alteration for both gels, in the samples containing carbopol gel there was color change and evaporation of part of the gel, while in methylcellulose the complete dehydration. Conclusions: The samples of the gels with hydroalcoholic extract of S. elegans and S. officinalis in concentrations of 5%, 2.5% and 1.25% obtained good stability according to the tests to which they were submit.